2023
DOI: 10.3390/plants12040890
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Components and Modes of the Methanol-Phase Extract from Commelina communis Linn

Abstract: Infectious diseases caused by pathogenic bacteria severely threaten human health. Traditional Chinese herbs are potential sources of new or alternative medicine. In this study, we analyzed for the first time antibacterial substances in the methanol-phase extract from a traditional Chinese herb—Commelina communis Linn—which showed an inhibition rate of 58.33% against 24 species of common pathogenic bacteria. The extract was further purified using preparative high-performance liquid chromatography (Prep-HPLC), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Based on our recent studies [ 11 , 12 , 13 , 14 ], the M–CE method was employed to extract antibacterial substances from the fruit of A. villosum Lour. Its water loss rate was 73.68% after freeze-drying at −80 °C for 48 h. The extraction yields of the MPE and chloroform-phase extract (CPE) of A. villosum Lour.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on our recent studies [ 11 , 12 , 13 , 14 ], the M–CE method was employed to extract antibacterial substances from the fruit of A. villosum Lour. Its water loss rate was 73.68% after freeze-drying at −80 °C for 48 h. The extraction yields of the MPE and chloroform-phase extract (CPE) of A. villosum Lour.…”
Section: Resultsmentioning
confidence: 99%
“…The bacterial strains and media used in this study are shown in Table S7 . The incubation conditions of the bacterial strains were the same as those described in our recent reports [ 11 , 12 , 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective antibacterial components were present in the ethyl acetate extract of C . communis Linn, with MICs of 10 mg/mL against Salmonella typhi , Escherichia coli , Staphylococcus aureus , and Staphylococcus albus [ 43 ].…”
Section: Pharmacological (Biological) Activities Of the Genus ...mentioning
confidence: 99%